HUBUNGAN POLA MAKAN DAN AKTIFITAS FISIK TERHADAP STATUS GIZI DI SISWA SMP AL-AZHAR PONTIANAK - Dwi Ayu Afrilia; Shelly Festilia A (Poltekkes Kemenkes Pontianak, 2018)
Nutritional problem is one public health problem that has not been fully addressed in the world. Combating the problem of malnutrition is not resolved nutritional problems arise, namely the rise in the incidence of obesity and chronic disease so that nutritional problems become more complex. Results RISKESDAS (Riset Kesehatan Dasar) in 2013 showed the prevalence of underweight 12.7% and 21.5% overweight for West Kalimantan, Pontianak prevalence at 5.2% fat and very wasted 4.8%.The purpose of this study to determine the relationship of diet and physical activity on the nutritional status of junior high school students of Al-Azhar Pontianak.This study was an observational study with cross sectional approach. The data collection being done with anthropometric measure to determine the nutritional status of students and using dietary questionnaires to determine the studentsâ€™ diets and physical activity questionnaires to determine physical activity in students.The results showed by nutritional status category with greater fat found in students with sufficient diet that is equal (19.4%). While students with greater nutritional status wasted contained in students with eating less is equal (20.8%). From the findings, it seemed that students with greater nutritional status found in students with mild activity (35.0%). While students with less nutritional status is also greater in students with mild activity (10.0%). Research shows there is a relationship between diet (p = 0.016), physical activityÂ Â (p = 0.021) on nutritional status in junior high school students of Al-Azhar Pontianak. The need for attention from parents to help control food intake of children so that children are not consuming excessive amounts of food can affect the nutritional status and Encourage students to undertake enough physical activity to prevent obesity.